PENGARUH PENERAPAN STRATEGI PEMECAHAN MASALAH DALAM PEMBELAJARAN MATEMATIKA TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VII SMP NEGERI 1 KANDIS - Nisa, Sahrun; ', Zuhri.D; ', Suhermi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This reseacrh startt from fact that the low of problem solving ability giving effect to mathematics learning outcomes. One cause is teacher did not give chance to accustom solving mathematic problem yet because some reason. So that, reserchers try to apply problem solving strategy that developed by G. Polya for increas problem solving ability. Kind of this research is The Static Group Comparison Study. Instrument for this researche is learning tools and the collect data instrument is probelm solving ability test. This research collected by test and analyze by statistic inferential, Mann-Withney. Outcomes from this research is applying of problem solving strategy give positive influence to problem solving ability in mathematics learning for VII grade student in SMP Negeri 1 Kandis Education Year 2015/2016.Keywords : Mathematics problem solving ability, Problem solving strategy, Pre-experiment